An inedited view of Naples by Jan van Essen: a general analysis of this work - Polo, Barbara (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2023)
During June 1676, the French-Dutch War was in its fourth year. Spain, which had sided with the Netherlands against France in 1673, had received reinforcements in 1675 from a Dutch squadron that went to the Mediterranean. The French, for their part, had managed to land in Messina, mutiny against Madrid. The battles of Messina (January 2, 1675), Stromboli (February 11, 1675), Alicudi (January 8, 1676) and Agosta (April 22) had ended with victories for the French fleet. During the last of them, the Dutch squadron, poorly supported by the Spanish forces, had been badly damaged and had lost its admiral, the prestigious Michiel de Ruyter. Consequently, the Spanish-Dutch fleet sought refuge. This painting, part of a private collection owned by the Alba´s house has been recently shown in a private meeting. It shows the Spanish-Dutch fleet, and not long after the Eighty Years’ War, the former opponents fought side by side against the French, off the city then under the Spanish rule. As other paintings show, that fleet was led by Michiel de Ruyter. In this painting, the author shows the Kingdom of Naples against French attacks. The painting shows the Viceroy of Naples paying tribute to de Ruyter’s fleet after it repulsed an initial attack at the Battle of Stromboli